Industrial training report: Kulim Advanced Technologies Sdn Bhd - Mohd Sukeri, Siti Nurdalila Hani (Universiti Teknologi MARA, Perlis, 2024)
My internship at Kulim Advanced Technologies Sdn.Bhd in Kulim, Kedah, from 4 April to 16 August 2024, was under the supervision of Puan Rohaida binti Salleh in the Human Resources Department. The company specializes in offering advanced engineering, consultancy, and training services. During this period, my role primarily involved assisting in events programs organized by the department and supporting the recruitment process. This included tasks such as calling candidates for interviews, coordinating schedules, and calculating allowances for employees participating in these events. Within Kulim Advanced Technologies, I gained valuable insights into the operational aspects of a company dedicated to technology development and human capital enhancement. Participating in events programs allowed me to understand the significance of employee engagement and the role of HR in fostering a positive work culture. In addition, involvement in the recruitment process provided practical experience in talent acquisition and management, reinforcing my interest in pursuing a career in Human Resources. My internship at Kulim Advanced Technologies was a rewarding experience that deepened my understanding of HR practices and their impact on organizational success. Working under the guidance of professionals like Puan Rohaida binti Salleh provided me with mentorship and support, contributing significantly to my professional growth. I am grateful for the opportunities and knowledge gained during my internship, which have prepared me for a successful career journey in Human Resources.